Sirtuins 1 and 2 in the Acute Period After Photothrombotic Stroke: Expression, Localization and Involvement in Apoptosis - Eid, Moez; Dzreyan, Valentina; Demyanenko, Svetlana (Frontiers in Physiology, 2022)
Sirtuins (SIRTs) are NAD+- dependent histone deacetylases. They are involved in numerous biological pathways and are considered a promising target for treating several human diseases. Although evidence is piling up to support the neuroprotective role of SIRTs in ischemic stroke, the role of different sirtuin isoforms needs further investigation. We studied the effects of photothrombotic stroke (PTS) on the expression and localization of sirtuins SIRT1 and SIRT2 in neurons and astrocytes of the penumbra and tested the activity of their selective and non-selective inhibitors. SIRT1 levels significantly decreased in the penumbra cells nuclei and increased in their cytoplasm. This indicated a redistribution of SIRT1 from the nucleus to the cytoplasm after PTS. The expression and intracellular distribution of SIRT1 were also observed in astrocytes. Photothrombotic stroke caused a sharp increase in SIRT2 levels in the cytoplasmic fraction of the penumbra neurons. SIRT2 was not expressed in the penumbra astrocytes. SIRT1 and SIRT2 did not co-localize with TUNEL-positive apoptotic cells. Mice were injected with EX-527, a selective SIRT1 inhibitor; SirReal2, selective SIRT2 inhibitor or salermide, a nonspecific inhibitor of SIRT1 and SIRT2. These inhibitors did not demonstrate any change in the infarction volume or the apoptotic index, compared to the control samples. The performed studies indicate the involvement of these sirtuins in the response of brain cells to ischemia in first 24 hours, but the growth of their expression and change in the localization of SIRT1 are not related to the regulation of penumbra cell apoptosis in acute period after PTS.